The stage of change and institution-building and its impact on the structure of housing policy in Iraq - الهماوندي, د.رافد عبد اللطيف; القيسي, ظبية فاروق (Journal of Planner and Development, 2010)
The research examines the reality of the housing sector in Iraq and the stage of change and institution-building, which is increasingly challenging to respond to development needs. The legal legislation in Iraq over the last five years indicates a significant shift towards decentralization, with powers and services being delegated from federal ministries to regional levels Localization and growth in cities and urban centers is an added factor that requires responses from local governments to strengthen the capacity of their institutions to engage in national policy debate at the regional and local levels. With the launch of the Ministry of Planning For a five-year national development, which seeks to expand the central resources at the same time working to build local authorities, it becomes necessary capacity of local councils to carry out developmental responsibilities development.In this context, the housing sector is one of the vital sectors of the national development plan, and since legal legislation in previous decades dealt with this sector as a demand and social activity, institutions and institutional frameworks reflect a central approach in dealing with housing needs based on production Housing units built by the public sector, and plots of land granted for the construction of housing in both cases did not provide a solution to the growing problem of the housing sector where there was no capacity to produce housing units parallel to the increase in the need for housing, and with the changes have become necessary to be here As structuring components affecting the housing sector, according to the vision of institutional and legislative changes. Such as the continued vision of housing as an expenditure on social services rather than as a productive and investment sector. The problem of research, while restoring the vision to the housing sector as a key driver of economic growth, job creation, wealth generation and individual investment is the main objective of the research, In cooperation with the relevant authorities in order to encourage, finance and build housing for all strata of the society in all its financial income, with special attention to housing of middle and low income people based on the hypothesis of research that the structure of components affecting the housing sector will lead to the role A larger product for the housing sector such as financial services, construction, reconstruction and investment.The results of the research revealed the identification of the axes of the confrontation with the formulation of a mechanism for the project of restructuring the housing sector with the required aspects of this process, which is the formulation of a modern housing policy and mobilization of resources to improve the housing sector in addition to activating the role of local councils in this sector.